Multi-level tensions in transport policy and planning : bus-rapid transit (BRT) in Indonesia : a dissertation presented in fulfilment of the requirements for the degree of Doctor of Philosophy (PhD) in Planning at Massey University, Palmerston North, New Zealand - Wijaya, Suryani Eka (Massey University, 2017)
International development agencies, supporting climate change sensitive transport policies in Low-Income Asian (LIA) cities, promote Bus Rapid Transit (BRT). However, these policies create tensions at the local level. Using a multi-level governance lens (MLG), this research examines the relations between and distribution of power among actors in BRT investment decisions in the two medium-sized Indonesian cities of Bandung and Surabaya. Analysis of policy and planning documents, and interviews with key stakeholders at central, provincial and city government levels highlighted financialinstitutional, socio-political and discursive tensions at multiple levels in BRT projects in these cities. The financial-institutional tensions resulted from city government funding dependency on central government and international development agencies that promoted BRT projects as low-cost ‘green’ solutions to traffic congestion and greenhouse gas emissions. Their “Go-green” campaign made it possible for Bandung and Surabaya governments to privilege BRT over traditional minibuses (angkot) and regular bus modes. The BRT projects were advanced through the low-cost, environmentally friendly and modern public transport discourses that did not get attention due to the absence of sitespecific narrative. Open communication and proactive public participation were also missing when undertaking BRT projects in Bandung and Surabaya so that the projects were opposed by social and political actors in both cities. As a result, national and provincial policies were modified in Bandung limiting BRT to two peri-urban corridors that do not meet local needs. In contrast, Surabaya accepted a BRT project, but then turned it down due to political and social pressure that developed during the process. This research identified the importance horizontal and vertical relationships in the BRT projects’ planning and implementation. While vertical alignment is important for translating national transport policy to local transport planning, horizontal integration and communication is crucial for transport project implementation. The mismatch between horizontal and vertical actors resulted in delays and ultimately rejection of BRT project in Surabaya and distortion of the BRT project in Bandung. This research identifies a need for integrated policy packages to help develop site-specific BRT projects for LIA cities. The evidence suggests a refinement for MLG theory in the context of LIA countries by taking into account the role of power and communication within the emerging economic, social and political pressures at the local level and the need to take into account the vital role of individual actors, institutions and planning process as they respond to and shape policies imposed by higher levels. It also identifies the important role of international level non-government organisations play in setting, or at least, influencing national and local policy agenda.
Keywords: Bus rapid transit; Planning; Urban transportation; Bandung; Surabaya; Indonesia